Engenhos de rapadura do Cariri: trabalho e cotidiano (1790-1850) - Oliveira, Antonio José de (2003)
This work analyzes activities of the rapaduras mills in the area of south of Ceará known like Cariri, in the period of 1790 to for 1850, evidencing the constitution and work dimensions and the daily. Analyzing inventories, sesmarias paetitions and travelers' chronicle, important considered aspects were discussed for the problematization of the research. The reading of those sources measured and aimed the particularities of the activity canavieira in the place: the importance of the migrations, the first towns, the types of built mills, several categories of workers and the slaves' importance. The performances that the social actors had in their daily and their relationships established in the ambit of the world of work were of fundamental relevance to the constitution of the social tessitura, polites and economic in the in its rural ambit. The real sense of the ownership of lends, of ranchesand of mills, it meant the control of some workes' categories, as well as it facilited who estopped those production means to enrich very quickly and to get to arrive on the top of the social pyramid in that daily one. It got us attention, also, the privileged gentlemem of mills, that dominated the políticaI and social landscape in the area. The mill went to its owner a kind of springboard to reach a patten of life anviable among the other existente social categories. Produced at those rudimentary mils, the rapadura was one of the main and very acceptable nutritious gender that the area produced, that became one of the products of high commercial value in the place. Its commercialization was fair efetuend in feiras of the main villas of the area.